Pengaruh self-efficacy, controllability dan norma subjektif terhadap intensi whistleblowing - Wahyu, Kartika; betari maharani (Politeknik Negeri Jakarta, 2023)
This study aims to examine the effect of Self Efficacy, Controllability and Subjective Norms on Whistleblowing Intentions. This study used a sample of employees who worked at Harapan Hospital, Magelang City. The number of samples in this study were 113 respondents. The sample selection was carried out using a non-probability sample selection method, namely purposive sampling. Testing the hypothesis in this study using multiple linear regression. The results of the study show that Self Efficacy has a positive effect on Whistleblowing Intentions, while the Controllability variables and Subjective Norms have no effect on Whistleblowing Intentions.